2020
DOI: 10.21203/rs.3.rs-102626/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cost-effectiveness of a Hybrid Emergency Room System for Severe Trauma: A health technology assessment from the perspective of the third-party payer in Japan

Abstract: Background Hybrid emergency room (ER) systems, consisting of an angiography-computed tomography (CT) machine in a trauma resuscitation room, are reported to be effective for reducing death from exsanguination in trauma patients. We aimed to investigate the cost-effectiveness of a hybrid ER system in severe trauma patients without severe traumatic brain injury (TBI). Methods We conducted a cost-utility analysis comparing the hybrid ER system to the conventional ER system from the perspective of the third-par… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Additionally, the transferred patients underwent TAE within a short duration, indicating that fast CT scanning can reduce decision-TAE time; hence, the development of fast imaging strategies is essential. Recent reports have suggested the effectiveness of hybrid emergency room systems (38,39), hybrid operation rooms (40), and mobile angiography systems (41) for treating patients with trauma. These systems consist of an angiography-CT machine in a trauma resuscitation room and have the potential to provide new evidence in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the transferred patients underwent TAE within a short duration, indicating that fast CT scanning can reduce decision-TAE time; hence, the development of fast imaging strategies is essential. Recent reports have suggested the effectiveness of hybrid emergency room systems (38,39), hybrid operation rooms (40), and mobile angiography systems (41) for treating patients with trauma. These systems consist of an angiography-CT machine in a trauma resuscitation room and have the potential to provide new evidence in this field.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the diagnostic studies included as part of the initial ATLS ® trauma survey are not well equipped to diagnose such a fatal vascular injury 37) . In addition, recent studies showed the efficacy of evaluation using whole CT during resuscitation in the hybrid ER, for even trauma patients with unstable circulation, in order to detect sites of hemorrhaging and facilitate the immediate performance procedures to obtain hemostasis [38][39][40][41] . Accordingly, to increase the survival rate of patients with fatal vascular injuries, such as blunt azygos injury, the early recognition of the site of hemorrhaging using CT and the immediate execution of surgical hemostasis in an appropriate position for modern surgeons (less experienced in the management of severe trauma) may be required, even when initial fluid resuscitation fails and unstable circulation remains.…”
Section: Discussionmentioning
confidence: 99%